Radiotherapy in cutaneous lymphomas: Recommendations from the EORTC cutaneous lymphoma tumour group - Elsayad, Khaled; Guenova, Emmanuella; Assaf, Chalid; Nicolay, Jan Peter; Trautinger, Franz; Stadler, Rudolf; Waldstein, Cora; Boterberg, Tom; Meijnders, Paul; Kirova, Youlia; Dobos, Gabor; Duque-Santana, Victor; et al. (European journal of cancer, 2024)
The number of primary cutaneous lymphoma patients receiving low-dose radiotherapy is increasing, though controlled clinical trials defining the standard radiation dose for each specific entity have not yet been completed. Radiation oncologists are left with making highly individualized decisions that would be better enriched by additional clinical evidence. In this expert opinion, we aim to provide a clear recommendation to improve the current practice of radiation oncology. In addition, existing literature has been reviewed to develop recommendations for all types of primary cutaneous lymphoma. A prospective trial is urgently needed to identify the factors influencing patient outcomes following different radiation doses.
Online verfügbar: 8. Oktober 2024, Artikelversion: 16. Oktober 2024
Gesehen am 28.04.2025